PENGARUH METODE BERMAIN SAINS SECARA SEDERHANA TERHADAP PERKEMBANGAN KOGINITIF ANAK DI KB. ALMIZAN DUSUN PLANGGARAN, DESA BRANTA TINGGI KECAMATAN TLANAKAN, KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Imroatul Mufida; M. Ridlwan; Ratno Abidin (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the effect of the simple science play method on the cognitive development of children in family planning. Al-Mizan, the hamlet ofPlanggaran, Branta Tinggi village, Tlanakan sub-district, Pamekasan district for the 2021/2022 school year. In particular, science games in kindergarten aim to make children have various scientific or scientific abilities. the more we open our minds to continue to study science, the more things we want to know about science. as well as the mindset of children who are always curious. The research method used in this study uses qualitative methods and purposive sampling. Where the determination of the research area is determined directly by the researcher himself, and the data collection in this method is the demonstration method. The results of the research that have been carried out, it can be concluded that, There is an effect of the simple method of playing science on the improvement of children's cognitive development in the Al-Mizan KB, Planggaran Hamlet, Branta Tinggi Village, Tlanakan District, Pamekasan Regency for the 2021/2022 Academic Year. Keywords: qualitative; demonstration method; science; purposive sampling